Evolution of Charge and Pair Density Modulations in Overdoped Bi_{2}Sr_{2}CuO_{6+δ} - Xintong Li; Changwei Zou; Ying Ding; Hongtao Yan; Shusen Ye; Haiwei Li; Zhenqi Hao; Lin Zhao; Xingjiang Zhou; Yayu Wang (Physical Review X, 2021)
One of the central issues concerning the mechanism of high-temperature superconductivity in cuprates is the nature of the ubiquitous charge order and its implications to superconductivity. Here, we use scanning tunneling microscopy to investigate the evolution of charge order from the optimally doped to strongly overdoped Bi_{2}Sr_{2}CuO_{6+δ} cuprates. We find that, with increasing hole concentration, the long-range checkerboard order gradually evolves into short-range glassy patterns consisting of diluted charge puddles. Each charge puddle has a unidirectional nematic internal structure and exhibits clear pair density modulations as revealed by the spatial variations of the superconducting coherence peak and gap depth. Both the charge puddles and the nematicity vanish completely in the strongly overdoped nonsuperconducting regime, when another type of short-range order with sqrt[2]×sqrt[2] periodicity emerges. These results shed important new light on the intricate interplay between the intertwined orders and the superconducting phase of cuprates.